2006
DOI: 10.1111/j.1439-0426.2006.00770.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary astaxanthin supplementation on reproductive characteristics of rainbow trout (Oncorhynchus mykiss)

Abstract: The effect of dietary astaxanthin supplementation on reproductive characteristics was investigated in five groups of female rainbow trout broodstock fed diets containing either 0.07, 12.46, 33.33, 65.06 or 92.91 mg astaxanthin kg )1 , respectively, and two groups of male rainbow trout broodstock fed diets supplemented with 0.07 and 33.33 mg astaxanthin kg )1 , respectively, for 6 months in an artificial photoperiod system until sexual maturation. The eggs from each group of female broodstock were divided into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
64
4
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(71 citation statements)
references
References 56 publications
0
64
4
3
Order By: Relevance
“…This finding conforms with the hypothesis proposed by Fitzpatrick et al (1995) that males choosing excessively ornamented females would receive fewer and/or poorer eggs than they could have obtained from a similar quality female which allocated less to ornamentation and more to reproduction. A possible physiological basis for our finding about the negative relationship between female redness and the early viability of her offspring could be that the development of carotenoid-based breeding coloration in females might reduce the availability of these valuable pigments (antioxidants) to developing embryos, thus leading to lower incubation success per brood (see e.g., Ahmadi et al 2006;Tyndale et al 2008). In support of this idea, Nordeide et al (2006Nordeide et al ( , 2008 found that the intensity of red ornamental coloration in both the stickleback and Arctic charr females may, indeed, be negatively correlated with the amount of carotenoids in the eggs, though the relationship was only marginally significant in the latter case.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…This finding conforms with the hypothesis proposed by Fitzpatrick et al (1995) that males choosing excessively ornamented females would receive fewer and/or poorer eggs than they could have obtained from a similar quality female which allocated less to ornamentation and more to reproduction. A possible physiological basis for our finding about the negative relationship between female redness and the early viability of her offspring could be that the development of carotenoid-based breeding coloration in females might reduce the availability of these valuable pigments (antioxidants) to developing embryos, thus leading to lower incubation success per brood (see e.g., Ahmadi et al 2006;Tyndale et al 2008). In support of this idea, Nordeide et al (2006Nordeide et al ( , 2008 found that the intensity of red ornamental coloration in both the stickleback and Arctic charr females may, indeed, be negatively correlated with the amount of carotenoids in the eggs, though the relationship was only marginally significant in the latter case.…”
Section: Discussionmentioning
confidence: 92%
“…In sockeye salmon (Oncorhynchus nerka Walbaum), for example, up to 85% of the total body carotenoids may be present in ripening eggs (Crozier 1970). Egg carotenoids are known to reduce the susceptibility of embryonic tissues to oxidative stress , and their positive effects on fertilization rates, early survival and early growth rates have been documented in fishes (Torrissen 1984;Salze et al 2005;Ahmadi et al 2006;Sawanboonchun et al 2008;Tyndale et al 2008) as well as in a wide range of other taxa (e.g., George et al 2001;McGraw et al 2005a). Consequently, there might be strong selection pressure on females to invest large amounts of these valuable resources to eggs, instead of 'wasting' them on ornaments and the question has been asked whether female colour may have evolved solely as a non-adaptive, correlated trait resulting from female selection for male colour in species expressing sexual coloration in both sexes (i.e., the genetic correlation hypothesis; Lande 1980;Amundsen 2000).…”
Section: Introductionmentioning
confidence: 98%
“…In rainbow trout O. mykiss , dietary supplements of astaxanthin are deemed necessary for optimum reproduction (Ahmadi et al . ). It has been claimed that astaxanthin triggers a speedier oocyte maturation in rainbow trout.…”
Section: Uses and Benefits Of Astaxanthinmentioning
confidence: 97%
“…In G. flavescens , there is no strong relationship between belly colouration and clutch size, but more colourful females lay eggs with higher carotenoid concentration (Svensson et al , 2006). Because carotenoids can improve embryonic development (Ahmadi et al , 2006), the male preference for colourful females in G. flavescens could be a strategy to obtain healthier offspring. Interestingly, A. minuta , which largely shares diet and life‐style with G. flavescens , had no detectable egg carotenoids.…”
Section: Discussionmentioning
confidence: 99%